VISUALISASI OBJEK WISATA BUKITTINGGI DALAM SENI LUKIS CORAK SURREALIS - ENGKY ANGRIAWAN, Drs. Erfahmi,M.Sn, Drs. Ir. Heldi, M.Si (Serupa The Journal of Art Education, 2015)
This thesis aims to visualize tourist attractions in Bukittinggi insurrealist paintings to introduce diversity and unique touristattractions Bukittinggi for the general public. Embodiment formssurrealist painting dominate forms, elongate, exalting andcombining attractions with other attractions in the media acrylic oncanvas in the style of surrealism. Method and steps in the processstart with the preparation, elaboration, synthesis, the realization ofthe concept to be presented to the public through exhibition. Thiswork provides information to the audience of the artwork on thevalues contained in the tourist attractions in Bukittinggi as thevalues of beauty, philosophy and history are illustrated through 10(ten) the title of surrealist painting.Kata Kunci: Objek Wisata, Bukittinggi, Seni Lukis, Surrealis